Efficacy and safety of pembrolizumab for the treatment of advanced or recurrent ovarian cancer: a meta-analysis based on single-arm studies - Mi, Xiaodong; Tan, Liming; Lin, Tong; Yang, Yimin; Liu, Hongmei; Tuo, Fei (Frontiers in Immunology, 2025)
ObjectiveOvarian cancer is a common malignant tumor of the female reproductive system, and traditional treatments are unsatisfactory due to its intraperitoneal spreading mechanism and its biologic characteristic of being prone to drug resistance. Pembrolizumab has demonstrated high objective remission and overall survival rates in a variety of solid tumors, and clinical trials are now available to explore its efficacy in the treatment of ovarian cancer. The objective of this systematic review and meta-analysis was to synthesize the findings of multiple clinical studies in order to evaluate the effectiveness and safety of the immunotherapeutic agent Pembrolizumab in patients diagnosed with advanced or recurrent ovarian cancer.MethodsA comprehensive search of literature published up to 19 November 2024 was conducted in the following databases: PubMed, Embase, Cochrane Library, Web of Science, Ovid_medline, Scopus, and ProQuest. The outcomes related to the administration of pembrolizumab in patients with advanced or recurrent ovarian cancer were extracted, including objective remission rate (ORR), disease control rate (DCR), overall survival (OS), progression-free survival (PFS), and treatment-related adverse events (AEs). A further meta-analysis was then performed.ResultsThis meta-analysis comprised 625 patients across nine studies. A total of 617 patients were involved in the efficacy assessment, while 592 patients were included in the safety assessment. The pooled analysis indicated an ORR of 24% (95% confidence interval [CI], 0.13–0.35), a DCR of 63% (95% CI, 0.49–0.77), a median progression-free survival (mPFS) of 4.82 months (95% CI, 3.29–6.35), and a median overall survival (mOS) of 13.54 months (95% CI, 10.35–16.73). Subgroup analysis indicated that the ORR in the PD-L1-positive group was 24% (95% CI, 0.12–0.36), while the ORR in the PD-L1-negative group was 18% (95% CI, 0.09–0.27). No statistically significant difference was observed between the two groups. The ORR was 26% (95% CI, 0.13–0.33) for patients administered a 200 mg dose every three weeks (q3w), while it was 12% (95% CI, 0.02–0.30) for those receiving a 10 mg/kg dose every two weeks (q2w). The overall incidence of adverse reactions of any grade was 81% (95% CI, 0.71–0.91), whereas the incidence of grade 3 or higher adverse reactions was 32% (95% CI, 0.09–0.54).ConclusionsThis meta-analysis indicates that pembrolizumab treatment for patients with advanced or recurrent ovarian cancer exhibits significant efficacy and an acceptable safety profile.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/ identifier CRD42024620116.